Karakter Biologi Isolat Trypanosoma evansi Asal Wabah di Sumba dan Implikasinya Setelah Dipasase Berulang pada Mencit - Sawitri, Dyah Haryuningtyas; Wardhana, April Hari (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Trypanosoma evansi, the agent of Surra, is a widely distributed blood protozoan infecting various species of livestock, pets and wild animals. So far, the biological character differences of T. evansi isolate from outbreak areas after re-passaging have not been reported. The aims of this study was to investigate characteristics of T. evansi collected from an outbreak area in 2012 in Sumba Island after re-passaging in mice based on pathogenicity.The study was divided into two steps of biological assays. Step 1 was addressed to observe the pathogenicity level of isolate compared to both high and low virulence controls. A total of 27 mice was divided into 9 groups (3 mice /group) e.g. negative control (KN); Positive control of high virulence (KBang87); Positive control of low virulence (KPml287); PI (Smb370); PII (Smb371); PIII (Smb372); PIV (Smb373); PV (Smb374) and PVI (Smb375). Step 2 was to look at the concistentcy of parasitemia level of isolates selected from step 1. A total of 21 mice was divided into 6 groups reinfected by Smb 372 (P VII, PVIII, PIX); Smb 375 (PX, PXI, PXII) and negative control. The results demonstrated that the parasitemia pattern of mice groups infected by Smb372 (PIII) and Smb375 (P VI) was similar to KBang87 (high virulence) and KPml287 (low virulence) group, respectively (Step 1). The step 2 results revealed that repassaging of the Smb372 isolate (PIII) in three different groups of mice (PVII, PVIII, PIX) showed similar parasitemia pattern with the origin isolates. However, the Smb375 had various parasitemia patterns among PX, PXI and PXII groups. They were moderate virulence (mixed high and low virulences) indicating that Smb375 was a mixed infection of T. evansi varians. Animals infected with either low or moderate virulence isolates need serious attention because they might act as potential reservoirs to infect other animals.